Crafting luxury : craftsmanship, manufacture, technology and the retail environment - Bloomfield, Mark; Borstrock, Shaun; Manlow, Veronica; Carta, Silvio (Intellect, The University of Chicago Press, 2022)
The idea of luxury has secured a place in contemporary western culture, and the term is now part of common parlance in both established and emerging economies. This book explores the many issues and debates surrounding the idea of luxury. 0This new research addresses contentious issues surrounding perceptions of luxury, its relationship to contemporary branding as created by the marketers, and the impact this has on the consumer and their purchasing habits.0Crafting Luxury considers work within the field of luxury and luxury brands, encompassing established companies with a long heritage: from conglomerates and small independents to 'new' luxury and emerging models with innovative practices. It examines the industry structures with respect to production, as well as the hierarchies that exist, and the impact these have on both internal and external perceptions of luxury, from the makers to the sellers and consumers alike. Attention is also given to the working structures of the ateliers, production facilities, origin of materials, manufacture and the impact of technology on consumption, the retail environment and sales, all providing a true insider's view of this complex world.0The authors - a designer of product and jewellery, a brand strategist and a fashion designer, an architect, and a sociologist and specialist in business management - are practitioners and academics. Their approach to dissecting the complex world of luxury brings distinct viewpoints to the debate, offering different perspectives, thoughts and interpretations of luxury.